Visualizing global properties of a molecular dynamics trajectory. Issue 1 (23rd November 2015) - Zhou, Hao; Li, Shangyang; Makowski, Lee
ABSTRACT: Molecular dynamics (MD) trajectories are very large data sets that contain substantial information about the dynamic behavior of a protein. Condensing these data into a form that can provide intuitively useful understanding of the molecular behavior during the trajectory is a substantial challenge that has received relatively little attention. Here, we introduce the sigma‐r plot, a plot of the standard deviation of intermolecular distances as a function of that distance. This representation of global dynamics contains within a single, one‐dimensional plot, the average range of motion between pairs of atoms within a macromolecule. Comparison of sigma‐r plots calculated from 10 ns trajectories of proteins representing the four major SCOP fold classes indicates diversity of dynamic behaviors which are recognizably different among the four classes. Differences in domain structure and molecular weight also produce recognizable features in sigma‐r plots, reflective of differences in global dynamics. Plots generated from trajectories with progressively increasing simulation time reflect the increased sampling of the structural ensemble as a function of time. Single amino acid replacements can give rise to changes in global dynamics detectable through comparison of sigma‐r plots. Dynamic behavior of substructures can be monitored by careful choice of interatomic vectors included in the calculation. These examples provide demonstrations of the utility of the sigma‐r plot to provide a simple measure of the global dynamics of a macromolecule. Proteins 2016; 84:82–91. © 2015 Wiley Periodicals, Inc.